ANALISIS PERUBAHAN PITA FREKUENSI 1800 DAN 2100 MHZ TERHADAP PERFORMANSI JARINGAN BASE TRANSCEIVER STATION - ., Syarif Muhammad Faisal (Faculty of Engineering, Universitas Tanjungpura, 2017)
Abstract - In its application, the mobile system has its limitationsÂ Â Â and isÂ Â Â oftenÂ Â Â experienced disturbancesÂ (interference) Â like Â limited Â talk channels as the result of the increasing number of cellular communication technology user, which is led to â€žblock callâ€Ÿ. The problem with Radio FrequencyÂ Â (RF)Â Â signalÂ Â receptionÂ Â isÂ Â alsoÂ Â an important factor in wireless communication system. The low quality of signal levels caused the frequent call failure or â€ždrop callâ€Ÿ. Therefore, it is necessary to have sustainable monitoring system and analysis towards the performance of theÂ network system, especially after the government produce the For a review of Necessary Process Monitoring and analysis of the Sustainable Network system, especially with the regulation of the Ministry of Communication Â and Â Information Â No. Â 19 Â / Â 2013 About Â